Entrepreneurial Development of Artisan in ODOP in Uttar Pradesh to Boost Economy: Strategies and New Approaches Towards Global Handicraft Index for Socio-Economic Welfare of Artisans. - Uma shankar yadav Yadav; Ravindra Tripathi; Mano Ashish Tripathi; Rajesh Kumar shastri; Gyan Prakash yadav; Aliza (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
ODOP can provide opportunity and have the capability to solve the migration problem of people from country to country, state to state by providing Local-level job and creativity and Have a great opportunity to make the Artisans as Entrepreneur and improve the social, economic situation of rural, weaker section unorganized workers and tribal people of the world especially in case of India because these people are facing huge challenges during lockdown period and stay at their home and hands are empty without money and Jobs. We should have to think to create our Local Talent and Traditional art and craft which are Sustainable Eco friendly and providing local market to Handicraft Sector for India to be an Atma nirbhar Bharat and Vocal for Local slogan of India. ODOP ‐ One District One Product scheme was Launched by the Uttar Pradesh government with The goal to help the local and block to help the artisan and also provide an enhance the access to the world market this scheme is a place that helps in connecting both sellers and buyers by handicraft and to gain the national and international recognition by marketing, branding, with easy credit by this scheme it will preserve our rich cultural heritage and tradition and unique skill at the district level. The economic situation of people involved in ODOP artisan work that is involved in handicraft sector 64 % artisan and worker are economical poor 23 % artisan and worker are not poor but they can run their craft at minimal level 17 prevent artisan are working as an entrepreneur.